Understanding learning and teaching : the experience in higher education - Prosser, Michael. (Society for Research into Higher Education and Open University Press, 1999)
Learning and Teaching in Higher Education. A Model for Understanding Learning and Teaching in Higher Education. Students' Prior Experiences of Learning. Students' Perceptions of Their Learning Situation. Students' Approaches to Learning. Students' Learning Outcomes. Experiences of Teaching in Higher Education. Understanding Learning and Teaching.